Efektivitas Dan Efisiensi Pelayanan Kesehatan Pada Puskesmas DTP Gununghalu - Wida, Widaningsih; Ida , Ida Jalilah Fitria (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study aims to determine the Effectiveness and Efficiency of Health Services at Puskesmas DTP Gununghalu. The research method used a qualitative descriptive approach with data collection techniques such as observation, interviews, and documentation. The informants were selected using purposive sampling technique. Based on the research findings, it can be concluded that the quality of services at Puskesmas DTP Gununghalu can be considered effective and efficient. The procedures carried out at the health center were optimal, as reflected in the high level of patient satisfaction. The service delivery time was efficient, the cost of healthcare was affordable, and the range of healthcare products provided was sufficient. The available facilities and infrastructure were adequate, and the competence of the service providers was aligned with their respective fields. As a recommendation, Puskesmas DTP Gununghalu can continuously improve the quality of services and provide a better experience for patients seeking healthcare.